HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONAL GURU DAN KOMPETENSI PEDAGOGIK GURU DENGAN PRESTASI BELAJAR - Chandra Praba Dwi Saputra; Pargito Pargito; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
This study aims to determine Relations Student Perceptions About Pedagogic Competence Professional Competence and Teacher Learning Achievement IPS In Class VIII Semester Students in Junior High School 17 Bandar Lampung. The population in this study were students in grade VIII A, B and C Junior High School 17 Belfast, amounting to 115 students, while samples taken as many as 46 students by using proportional random sampling techniques of data collection techniques using the techniques of documentation, observation and questionnaires. Prior to further analysis of data in the test for normality and homogeneity and then analyzes the data using a product moment correlation formula used in all hypothesis testing that has been formulated. Based on the analysis of the data obtained the following results: A. There is a close positive relationship and significant correlation between students 'perceptions about the professional competence of teachers to students' learning achievements IPS VIII semester grade Junior High School 17 Belfast TP 2010/2011. This is demonstrated by calculating r = 0.16 r table = 0297 with a significant level of 5% where db = n-2 = 44. The better the students 'perceptions about the professional competence of teachers, the students' learning achievements IPS tend to the better. 2. There is a close positive relationship and significant correlation between student perceptions of pedagogical competence of teachers with classroom learning achievement IPS VIII semester students of SMP Negeri 17 Bandar Lampung TP 2010/2011. This is indicated by r count = 0440 = 0297 r table with a significant level of 5% where db = n-2 = 44. The better the students 'perceptions of teachers' pedagogic competence, then the IPS student learning achievement likely the better. 3. There is a close positive relationship and significant correlation between students 'perceptions about the professional competence of teachers and pedagogical competence of teachers to students' learning achievements IPS VIII semester grade Junior High School 17 Belfast TP 2010/2011. This is indicated by r count = 0654 = 0297 r table with a significant level of 5% where db = n-2 = 44. The better the students 'perceptions about the professional competence of teachers and pedagogical competence of teachers, the students' learning achievements IPS tend to the better. Key words: Perceptions of Students, Teacher Competencies, Learning Achievement